Novel environment-friendly temperature-resistant fireproof coating and preparation method thereof
By using new environmentally friendly and heat-resistant fire-resistant coatings with specific components and ratios, a high-density flame-retardant layer is formed, which solves the problems of insufficient heat resistance and short continuous temperature resistance of existing fire-resistant coatings in high temperature environments, and achieves the effect of maintaining fire-resistant performance for a long time at high temperatures above 1500℃.
Patent Information
- Application Number
- CN202411889352.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-14
AI Technical Summary
The existing fire-retardant coatings are insufficient in high-temperature environments and have a short continuous temperature resistance time, which makes it impossible to effectively protect the steel structure in fire.
A new environmentally friendly and heat-resistant fire-retardant coating consisting of silicon carbide, silicate, diatomaceous earth, kaolinite, alumina, ceramic micropowder, sodium fluorosilicate, acrylic emulsion, silicone resin, sodium zirconate and other components is used to form a flame retardant layer with high density and stability through specific ratios and preparation methods.
The fire-retardant coating does not change color or fall off at high temperatures above 1500℃, and the continuous temperature resistance time exceeds 2.5 hours. It has good flame retardant effect and physical and mechanical properties, which significantly improves the protection performance of the steel structure in fire.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fireproof coatings, in particular to a novel environmentally friendly heat-resistant fireproof coating and a preparation method thereof. Background Art
[0002] Building fire protection is an important field of fire science and technology, and fire retardant coatings are an important part of fireproof building materials. High temperature resistant coatings are also called heat resistant coatings. Generally, they refer to high-quality coatings that do not change color, do not fall off, have no irritating odor, are non-toxic, have good flame retardant effects, and maintain physical and mechanical properties above 200°C. Steel structure is one of the main building structures at present. When the fire temperature reaches above 600°C, its structural strength will drop rapidly, thus affecting the bearing capacity of the building and causing the building to collapse in the fire. At present, fire retardant coatings are usually applied on the surface of steel structures to improve the heat resistance of steel structures in fires, so as to reduce or avoid the damage of fires to the building structures. However, most of the existing fire retardant coatings have the problem of low heat resistance, usually below 900°C, and the continuous heat resistance basically does not exceed 2.5 hours. However, the temperature of most fire scenes can be as high as 700°C or above. Therefore, the current protective performance of fire retardant coatings for steel structure buildings is still insufficient, and it is necessary to further improve the protective performance of fire retardant coatings. Summary of the invention
[0003] To this end, the technical problem to be solved by the present invention is to provide a new type of environmentally friendly heat-resistant fire-retardant coating and a preparation method thereof, which can withstand temperatures above 1500°C, has poor thermal conductivity, good flame retardant effect, is non-toxic at high temperatures, produces no irritating odor, and can withstand continuous temperatures for more than 2.5 hours without changing physical and mechanical properties, so as to solve the technical problems of existing fire-retardant coatings such as poor high temperature resistance and short continuous temperature resistance time.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0005] A novel environmentally friendly heat-resistant fireproof coating is composed of the following components in parts by weight: 10-13 parts by weight of silicon carbide, 23-27 parts by weight of silicate, 8-12 parts by weight of diatomaceous earth, 6-8 parts by weight of kaolinite, 10-12 parts by weight of aluminum oxide, 6-9 parts by weight of ceramic micropowder, 20-25 parts by weight of sodium fluorosilicate, 20-22 parts by weight of acrylic emulsion, 15-18 parts by weight of organic silicon resin, 10-13 parts by weight of sodium zirconate, 6-8 parts by weight of diluent, 2-3 parts by weight of stabilizer, 1-1.5 parts by weight of suspending agent, 1-3 parts by weight of adhesive and 1-3 parts by weight of rust dissolving agent.
[0006] The fire retardant coating has the following advantages: (1) Environmental protection: no irritating odor is generated when it is baked for more than 2.5 hours in an environment with a continuous high temperature greater than or equal to 1500°C; (2) High temperature resistance: it does not change color, fall off, or maintain physical and mechanical properties at a high temperature greater than or equal to 1500°C; (3) Fire prevention: it can prevent fires from occurring, block the spread of fires, protect structures coated with the coating, delay damage, and gain time for firefighting. It is an ideal new building material for the future construction industry.
[0007] In the above-mentioned novel environmentally friendly heat-resistant fireproof coating, the silicate is aluminum silicate and potassium silicate mixed in a mass ratio of 1:1 to 2.5; the silicate is sieved through a 300-mesh sieve. Aluminum silicate and potassium silicate are mixed in this ratio and used in the fireproof coating of the present invention, and can significantly improve the compactness and stability of the flame retardant layer formed by the fireproof coating in a high temperature environment by synergistically working with other components.
[0008] The diatomite in the novel environmentally friendly heat-resistant fire-retardant coating is a mixture of diatomite with a particle size of 5 to 15 μm and diatomite with a particle size of 20 to 40 μm in a mass ratio of 1:2 to 3; the diatomite with the particle size distribution in the fire-retardant coating of the present invention works in synergy with other components to fully improve the high temperature resistance of the fire-retardant coating. Silicon carbide, aluminum oxide and ceramic micropowder are all sieved with a 300 mesh sieve; the particle size of kaolinite is 50 to 200 nm.
[0009] The new environmentally friendly heat-resistant fireproof coating has a solid content of 35-50% of acrylic emulsion; the silicone resin is one or a mixture of two or more polyalkyl aryl silicone resins; and both sodium fluorosilicate and sodium zirconate are sieved through a 300-mesh sieve.
[0010] The new environmentally friendly heat-resistant fire-retardant coating has acrylic acid as the diluent, calcium stearate as the stabilizer, sodium hydroxymethyl cellulose as the suspending agent, polyester phosphate as the adhesive, and hydrofluoric acid as the rust-dissolving agent.
[0011] A method for preparing a novel environmentally friendly heat-resistant fire-retardant coating comprises the following steps:
[0012] Step (1), 10 to 13 parts by weight of silicon carbide, 23 to 27 parts by weight of silicate, 8 to 12 parts by weight of diatomaceous earth, 6 to 8 parts by weight of kaolinite, 10 to 12 parts by weight of alumina and 6 to 9 parts by weight of ceramic powder are mixed and stirred to obtain a mixed powder;
[0013] Step (2), 20 to 25 parts by weight of sodium fluorosilicate, 20 to 22 parts by weight of acrylic emulsion, 15 to 18 parts by weight of silicone resin, 10 to 13 parts by weight of sodium zirconate, 6 to 8 parts by weight of diluent, 2 to 3 parts by weight of stabilizer, 1 to 1.5 parts by weight of suspending agent, 1 to 3 parts by weight of adhesive and 1 to 3 parts by weight of rust dissolving agent are mixed and stirred to obtain a mixed liquid;
[0014] Step (3), when in use, the mixed powder prepared in step (1) and the mixed liquid prepared in step (2) are mixed and stirred evenly to obtain a new environmentally friendly heat-resistant fire-retardant coating.
[0015] The preparation method of the novel environmentally friendly heat-resistant fire-retardant coating, in step (1): the silicate is a mixture of aluminum silicate and potassium silicate in a mass ratio of 1:1-2.5; the silicate is sieved through a 300-mesh sieve; the diatomaceous earth is a mixture of diatomaceous earth with a particle size of 5-15 μm and diatomaceous earth with a particle size of 20-40 μm in a mass ratio of 1:2-3; silicon carbide, aluminum oxide and ceramic micropowder are all sieved through a 300-mesh sieve; the particle size of kaolinite is 50-200 nm;
[0016] In step (2), the solid content of the acrylic emulsion is 35-50%; the silicone resin is one or a mixture of two or more polyalkyl aryl silicone resins; sodium fluorosilicate and sodium zirconate are both sieved through a 300-mesh sieve; the diluent is acrylic acid; the stabilizer is calcium stearate; the suspending agent is sodium hydroxymethyl cellulose; the adhesive is polyester phosphate; and the rust dissolving agent is hydrofluoric acid.
[0017] In the preparation method of the above-mentioned novel environmentally friendly heat-resistant fire-retardant coating, in step (2), the preparation method of the acrylic emulsion is:
[0018] Step (2-1), firstly adding sodium dodecylbenzene sulfonate and nano silicon oxide powder into water, heating and stirring to obtain a mixed suspension; then simultaneously adding butyl acrylate, methacrylic acid, ethylene glycol dimethacrylate, acrylamide and vinyl trimethoxysilane dropwise into the mixed suspension and stirring to obtain a pre-emulsion;
[0019] Step (2-2), firstly adding sodium dodecylbenzene sulfonate into water, heating and stirring to mix, to obtain a translucent solution; then simultaneously adding butyl acrylate, methacrylic acid, ethylene glycol dimethacrylate, acrylamide and ammonium persulfate solution dropwise into the translucent solution and stirring to obtain a seed emulsion;
[0020] Step (2-3), raising the temperature of the seed emulsion, and simultaneously dropping the ammonium persulfate solution and the pre-emulsion prepared in step (2-1) into the seed emulsion and keeping the temperature, and naturally cooling to room temperature after the reaction is completed, thereby obtaining an acrylic emulsion.
[0021] The preparation method of the above-mentioned novel environmentally friendly heat-resistant fire-retardant coating comprises the following steps: in step (2-1), the temperature of the mixed suspension is controlled to be 45-55° C. during the entire operation process; the mass fraction of sodium dodecylbenzene sulfonate in the mixed suspension is 7-10wt%, the mass fraction of nano silicon oxide powder is 10-15wt%, and the particle size of the nano silicon oxide powder is 20-50nm; the mass ratio of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate is 1:(0.5-1):(0.05-0.1); the amount of acrylamide used is 2-3% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the amount of vinyl trimethoxysilane used is 5-6% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate;
[0022] In step (2-2), the temperature of the translucent solution is controlled to be 60-70° C. during the entire operation process; in the translucent solution, the mass fraction of sodium dodecylbenzene sulfonate is 7-10wt%; the mass ratio of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate is 1:(0.5-1):(0.05-0.1); the amount of acrylamide used is 2-3% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the amount of ammonium persulfate solution used is 0.5-1.0% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the ammonium persulfate solution is an ammonium persulfate aqueous solution with a mass fraction of 10wt%;
[0023] In step (2-3), the temperature of the seed emulsion is increased to 80-90° C., the amount of the ammonium persulfate solution is 2-3% of the total mass of the seed emulsion; the ammonium persulfate solution is an ammonium persulfate aqueous solution with a mass fraction of 10wt%; and the mass ratio of the pre-emulsion to the seed emulsion is 1:5-10.
[0024] The preparation method of the novel environmentally friendly heat-resistant fire-retardant coating, in step (1): the silicate is a mixture of aluminum silicate and potassium silicate in a mass ratio of 1:1.5; the silicate is sieved through a 300-mesh sieve; the diatomaceous earth is a mixture of diatomaceous earth with a particle size of 5 to 15 μm and diatomaceous earth with a particle size of 20 to 40 μm in a mass ratio of 1:3; silicon carbide, aluminum oxide and ceramic micropowder are all sieved through a 300-mesh sieve; the particle size of kaolinite is 50 to 200 nm;
[0025] In step (2), the organosilicon resin is one or a mixture of two or more polyalkyl aryl organosilicon resins; sodium fluorosilicate and sodium zirconate are both sieved through a 300-mesh sieve; the diluent is acrylic acid; the stabilizer is calcium stearate; the suspending agent is sodium hydroxymethyl cellulose; the adhesive is polyester phosphate; the rust dissolving agent is hydrofluoric acid; and the preparation method of the acrylic emulsion is:
[0026] Step (2-1), firstly adding sodium dodecylbenzene sulfonate and nano silicon oxide powder into water, heating to 50° C. and stirring to obtain a mixed suspension; the mass fraction of sodium dodecylbenzene sulfonate in the mixed suspension is 8wt%, the mass fraction of nano silicon oxide powder is 15wt%, and the particle size of the nano silicon oxide powder is 20 to 50nm;
[0027] Then, butyl acrylate, methacrylic acid, ethylene glycol dimethacrylate, acrylamide and vinyl trimethoxysilane are simultaneously added dropwise to the mixed suspension within 30 minutes and stirred evenly to obtain a pre-emulsion; the mass ratio of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate is 1:0.5:0.08; the amount of acrylamide is 3% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the amount of vinyl trimethoxysilane is 6% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate;
[0028] Step (2-2), firstly adding sodium dodecylbenzene sulfonate into water, heating to 70° C. and stirring to obtain a translucent solution; in the translucent solution, the mass fraction of sodium dodecylbenzene sulfonate is 10wt%;
[0029] Then, butyl acrylate, methacrylic acid, ethylene glycol dimethacrylate, acrylamide and ammonium persulfate solution are simultaneously added dropwise to the translucent solution and stirred evenly to obtain a seed emulsion; the mass ratio of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate is 1:0.5:0.08; the amount of acrylamide is 3% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the amount of ammonium persulfate solution is 1.0% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the ammonium persulfate solution is an ammonium persulfate aqueous solution with a mass fraction of 10wt%;
[0030] Step (2-3), raising the temperature of the seed emulsion to 90° C., and simultaneously dropping a 10wt% ammonium persulfate solution and the pre-emulsion prepared in step (2-1) into the seed emulsion and keeping the temperature for 30 minutes, and naturally cooling to room temperature after the reaction is completed, so as to obtain an acrylic emulsion; the amount of the ammonium persulfate solution is 3% of the total mass of the seed emulsion; and the mass ratio of the amount of the pre-emulsion to the seed emulsion is 1:7.
[0031] The technical solution of the present invention achieves the following beneficial technical effects:
[0032] 1. The novel environmentally friendly heat-resistant fire-retardant coating of the present invention has the advantages of being environmentally friendly, non-toxic, safe to use and operate, and not producing toxic gases when exposed to high temperatures. According to tests, the thermal conductivity of the fire-retardant coating of the present invention is less than 0.03W / mK, and it can withstand a high temperature of 1500°C for more than 2.5 hours, and no irritating odor is found, that is, the fire-retardant coating directly faces the flame for more than 2.5 hours and still exhibits good fire resistance.
[0033] 2. The fire retardant coating prepared by the preparation method of the novel environmentally friendly heat-resistant fire retardant coating of the present invention has the advantages of anti-oxidation, acid resistance, impact resistance and non-falling at room temperature. Applying it on high-temperature heated metal can significantly reduce the heating temperature of the metal, so that the metal can be away from the metal phase boundary change, so that the metal structure can maintain the strength, toughness, strain, etc. at room temperature under high temperature environment.
[0034] 3. Compared with the commercially available acrylic emulsion, the fire retardant coating prepared by mixing the self-made acrylic emulsion of the present invention with other components of the fire retardant coating of the present invention has a significantly improved high temperature resistance limit and a significantly reduced thermal conductivity. When preparing the acrylic emulsion, the present invention adds a specific proportion of vinyl trimethoxy silane (organic silicon) and 20-50nm nano silicon oxide powder (inorganic silicon) to modify it to obtain a "silicon-modified acrylic emulsion". When the "silicon-modified acrylic emulsion" prepared by the method of the present invention is mixed with other components of the fire retardant coating of the present invention and then coated on a steel structure, the "silicon-modified acrylic emulsion" can form a highly adherent and dense fireproof layer on the surface of the steel structure with the film-forming substances in other components (especially potassium silicate in silicate); when the fireproof layer encounters high temperature in the fire scene, it can quickly carbonize to form a flame retardant and heat-insulating layer, and the carbonized flame retardant and heat-insulating layer still has strong adhesion and good density on the surface of the steel structure, so it can significantly enhance the fireproof performance of the fire retardant coating. However, when a fire retardant coating is prepared by mixing a commercially available acrylic emulsion with other components of the fire retardant coating of the present invention, no matter how the ratio of the components is adjusted, the adhesion and density of the flame retardant and heat-insulating layer formed by carbonization of the fire retardant coating at high temperature are greatly reduced, so the fire retardant performance of the fire retardant coating is poor; however, the specific reasons for this result are still unclear and are still under analysis and research. DETAILED DESCRIPTION
[0035] Example 1
[0036] In this embodiment, the new environmentally friendly heat-resistant fire-retardant coating is composed of the following components by weight: 13 kg of silicon carbide, 25 kg of silicate (including 10 kg of aluminum silicate and 15 kg of potassium silicate), 12 kg of diatomaceous earth (4 kg of diatomaceous earth with a particle size of 5 to 15 μm and 8 kg of diatomaceous earth with a particle size of 20 to 40 μm), 8 kg of nano kaolinite (particle size of 50 to 200 nm), 12 kg of alumina, 9 kg of ceramic micropowder, 25 kg of sodium fluorosilicate, 22 kg of acrylic emulsion, 18 kg of silicone resin, 12 kg of sodium zirconate, 8 kg of diluent, 3 kg of stabilizer, 1 kg of suspending agent, 1 kg of adhesive, and 2 kg of rust dissolving agent.
[0037] In this embodiment, silicon carbide, aluminum oxide, ceramic powder, sodium fluorosilicate and sodium zirconate are all sieved through a 300-mesh sieve; the silicone resin is a polyalkyl aryl silicone resin; the acrylic emulsion is a commercially available acrylic emulsion with a solid content of 47% and a pH of 8; the diluent is acrylic acid; the stabilizer is calcium stearate; the suspending agent is sodium hydroxymethyl cellulose; the adhesive is polyester phosphate; and the rust-dissolving agent is hydrofluoric acid.
[0038] The preparation method of the novel environmentally friendly heat-resistant fire-retardant coating of this embodiment comprises the following steps:
[0039] Step (1), mixing silicon carbide, silicate, diatomaceous earth, kaolinite, alumina and ceramic powder according to the above weight ratio and stirring evenly to obtain a mixed powder;
[0040] Step (2), mixing and stirring the sodium fluorosilicate, acrylic emulsion, silicone resin, sodium zirconate, diluent, stabilizer, suspending agent, adhesive and rust dissolving agent in the above weight ratio to obtain a mixed liquid;
[0041] Step (3), when in use, the mixed powder prepared in step (1) and the mixed liquid prepared in step (2) are mixed and stirred evenly to obtain the new environmentally friendly heat-resistant fire-retardant coating of this embodiment.
[0042] In some other embodiments, the mixed powder and the mixed liquid can also be packaged at 50 kg / bag and mixed according to the proportion when used. The fire retardant coating prepared in this embodiment is quick-drying and the quick-drying time is less than 2 hours. High-pressure spraying and manual brushing can be used during the construction process.
[0043] Example 2
[0044] The difference between this embodiment and embodiment 1 is that the acrylic emulsion is prepared by the following steps:
[0045] Step (2-1), firstly adding sodium dodecylbenzene sulfonate and nano silicon oxide powder into water, heating to 50° C. and stirring to obtain a mixed suspension; the mass fraction of sodium dodecylbenzene sulfonate in the mixed suspension is 8wt%, the mass fraction of nano silicon oxide powder is 15wt%, and the particle size of the nano silicon oxide powder is 20 to 50nm;
[0046] Then, butyl acrylate, methacrylic acid, ethylene glycol dimethacrylate, acrylamide and vinyl trimethoxysilane are simultaneously added dropwise to the mixed suspension within 30 minutes and stirred evenly to obtain a pre-emulsion; the mass ratio of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate is 1:0.5:0.08; the amount of acrylamide is 3% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the amount of vinyl trimethoxysilane is 6% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate;
[0047] Step (2-2), firstly adding sodium dodecylbenzene sulfonate into water, heating to 70° C. and stirring to obtain a translucent solution; in the translucent solution, the mass fraction of sodium dodecylbenzene sulfonate is 10wt%;
[0048] Then, butyl acrylate, methacrylic acid, ethylene glycol dimethacrylate, acrylamide and ammonium persulfate solution are simultaneously added dropwise to the translucent solution and stirred evenly to obtain a seed emulsion; the mass ratio of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate is 1:0.5:0.08; the amount of acrylamide is 3% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the amount of ammonium persulfate solution is 1.0% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the ammonium persulfate solution is an ammonium persulfate aqueous solution with a mass fraction of 10wt%;
[0049] Step (2-3), raising the temperature of the seed emulsion to 90° C., and simultaneously dropping a 10wt% ammonium persulfate solution and the pre-emulsion prepared in step (2-1) into the seed emulsion and keeping the temperature for 30 minutes, and naturally cooling to room temperature after the reaction is completed, so as to obtain an acrylic emulsion; the amount of the ammonium persulfate solution is 3% of the total mass of the seed emulsion; and the mass ratio of the amount of the pre-emulsion to the seed emulsion is 1:7.
[0050] The fire retardant coatings in Example 1 and Example 2 were tested for performance, including thermal conductivity, adhesion, adhesion after high temperature, and temperature resistance. The specific results are shown in the following table:
[0051] Table 1
[0052]
[0053] In this embodiment, the performance after high temperature refers to the performance maintained at 1500°C for 10 hours. In fact, in order to clarify the temperature resistance limit of the fire retardant coating in Example 2, the fire retardant coating of Example 2 was also tested at 1800°C. The results showed that the coating remained intact without discoloration after being maintained for 2.5 hours, and there was no obvious change in the coating after being maintained for 5 hours.
[0054] The fire retardant coatings of Example 1 and Example 2 were applied to steel plates by manual brushing to test the thermal insulation performance. A cone calorimeter was used with a heat radiation power of 80 Kw / m 2 The test was conducted, during which the bottom of the cone calorimeter was 25 mm away from the coating surface. Test results: Under the protection of the fire retardant coating of Example 1, the time taken for the steel plate temperature to reach 300°C was 1397 seconds, and under the protection of the fire retardant coating of Example 2, the time taken for the steel plate temperature to reach 300°C was 1469 seconds.
[0055] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A new type of environmentally friendly heat-resistant fire-retardant coating, characterized in that: The invention is composed of the following components in parts by weight: 10 to 13 parts by weight of silicon carbide, 23 to 27 parts by weight of silicate, 8 to 12 parts by weight of diatomaceous earth, 6 to 8 parts by weight of kaolinite, 10 to 12 parts by weight of aluminum oxide, 6 to 9 parts by weight of ceramic micropowder, 20 to 25 parts by weight of sodium fluorosilicate, 20 to 22 parts by weight of acrylic emulsion, 15 to 18 parts by weight of organic silicon resin, 10 to 13 parts by weight of sodium zirconate, 6 to 8 parts by weight of diluent, 2 to 3 parts by weight of stabilizer, 1 to 1.5 parts by weight of suspending agent, 1 to 3 parts by weight of adhesive and 1 to 3 parts by weight of rust dissolving agent.
2. The method for preparing the novel environmentally friendly heat-resistant fire-retardant coating according to claim 1, characterized in that: The silicate is a mixture of aluminum silicate and potassium silicate in a mass ratio of 1:1 to 2.5; the silicate is sieved through a 300-mesh sieve.
3. The method for preparing the novel environmentally friendly heat-resistant fire-retardant coating according to claim 1, characterized in that: The diatomaceous earth is prepared by mixing diatomaceous earth with a particle size of 5 to 15 μm and diatomaceous earth with a particle size of 20 to 40 μm in a mass ratio of 1:2 to 3; silicon carbide, alumina and ceramic micropowder are all sieved through a 300-mesh sieve; and the particle size of kaolinite is 50 to 200 nm.
4. The method for preparing the novel environmentally friendly heat-resistant fire-retardant coating according to claim 1, characterized in that: The solid content of the acrylic emulsion is 35-50%; the organic silicon resin is one or a mixture of two or more polyalkyl aryl organic silicon resins; and the sodium fluorosilicate and the sodium zirconate are both sieved through a 300-mesh sieve.
5. The method for preparing the novel environmentally friendly heat-resistant fire-retardant coating according to claim 1, characterized in that: The diluent is acrylic acid; the stabilizer is calcium stearate; the suspending agent is sodium hydroxymethyl cellulose; the adhesive is polyester phosphate; and the rust dissolving agent is hydrofluoric acid.
6. A method for preparing a novel environmentally friendly heat-resistant fire-retardant coating, characterized in that: The steps include: Step (1), 10 to 13 parts by weight of silicon carbide, 23 to 27 parts by weight of silicate, 8 to 12 parts by weight of diatomaceous earth, 6 to 8 parts by weight of kaolinite, 10 to 12 parts by weight of alumina and 6 to 9 parts by weight of ceramic powder are mixed and stirred to obtain a mixed powder; Step (2), 20 to 25 parts by weight of sodium fluorosilicate, 20 to 22 parts by weight of acrylic emulsion, 15 to 18 parts by weight of silicone resin, 10 to 13 parts by weight of sodium zirconate, 6 to 8 parts by weight of diluent, 2 to 3 parts by weight of stabilizer, 1 to 1.5 parts by weight of suspending agent, 1 to 3 parts by weight of adhesive and 1 to 3 parts by weight of rust dissolving agent are mixed and stirred to obtain a mixed liquid; Step (3): When in use, the mixed powder prepared in step (1) and the mixed liquid prepared in step (2) are mixed and stirred evenly to obtain the new environmentally friendly heat-resistant fire-retardant coating as claimed in claim 1.
7. The method for preparing the novel environmentally friendly heat-resistant fire-retardant coating according to claim 6, characterized in that: In step (1), the silicate is a mixture of aluminum silicate and potassium silicate in a mass ratio of 1:1 to 2.5; the silicate is sieved through a 300-mesh sieve; the diatomaceous earth is a mixture of diatomaceous earth with a particle size of 5 to 15 μm and diatomaceous earth with a particle size of 20 to 40 μm in a mass ratio of 1:2 to 3; silicon carbide, aluminum oxide and ceramic micropowder are all sieved through a 300-mesh sieve; the particle size of kaolinite is 50 to 200 nm; In step (2), the solid content of the acrylic emulsion is 35-50%; the silicone resin is one or a mixture of two or more polyalkyl aryl silicone resins; sodium fluorosilicate and sodium zirconate are both sieved through a 300-mesh sieve; the diluent is acrylic acid; the stabilizer is calcium stearate; the suspending agent is sodium hydroxymethyl cellulose; the adhesive is polyester phosphate; and the rust dissolving agent is hydrofluoric acid.
8. The method for preparing the novel environmentally friendly heat-resistant fire-retardant coating according to claim 6, characterized in that: In step (2), the preparation method of acrylic emulsion is: Step (2-1), firstly adding sodium dodecylbenzene sulfonate and nano silicon oxide powder into water, heating and stirring to obtain a mixed suspension; then simultaneously adding butyl acrylate, methacrylic acid, ethylene glycol dimethacrylate, acrylamide and vinyl trimethoxysilane dropwise into the mixed suspension and stirring to obtain a pre-emulsion; Step (2-2), firstly adding sodium dodecylbenzene sulfonate into water, heating and stirring to mix, to obtain a translucent solution; then simultaneously adding butyl acrylate, methacrylic acid, ethylene glycol dimethacrylate, acrylamide and ammonium persulfate solution dropwise into the translucent solution and stirring to obtain a seed emulsion; Step (2-3), raising the temperature of the seed emulsion, and simultaneously dropping the ammonium persulfate solution and the pre-emulsion prepared in step (2-1) into the seed emulsion and keeping the temperature, and naturally cooling to room temperature after the reaction is completed, thereby obtaining an acrylic emulsion.
9. The method for preparing the novel environmentally friendly heat-resistant fire-retardant coating according to claim 8, characterized in that: In step (2-1), the temperature of the mixed suspension is controlled to be 45-55° C. during the entire operation process; the mass fraction of sodium dodecylbenzene sulfonate in the mixed suspension is 7-10wt%, the mass fraction of nano-silicon oxide powder is 10-15wt%, and the particle size of the nano-silicon oxide powder is 20-50nm; the mass ratio of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate is 1:(0.5-1):(0.05-0.1); the amount of acrylamide is 2-3% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the amount of vinyl trimethoxysilane is 5-6% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; In step (2-2), the temperature of the translucent solution is controlled to be 60-70° C. during the entire operation process; in the translucent solution, the mass fraction of sodium dodecylbenzene sulfonate is 7-10wt%; the mass ratio of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate is 1:(0.5-1):(0.05-0.1); the amount of acrylamide used is 2-3% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the amount of ammonium persulfate solution used is 0.5-1.0% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the ammonium persulfate solution is an ammonium persulfate aqueous solution with a mass fraction of 10wt%; In step (2-3), the temperature of the seed emulsion is increased to 80-90° C., the amount of the ammonium persulfate solution is 2-3% of the total mass of the seed emulsion; the ammonium persulfate solution is an ammonium persulfate aqueous solution with a mass fraction of 10wt%; and the mass ratio of the pre-emulsion to the seed emulsion is 1:5-10.
10. The method for preparing the novel environmentally friendly heat-resistant fire-retardant coating according to claim 6, characterized in that: In step (1), the silicate is a mixture of aluminum silicate and potassium silicate in a mass ratio of 1:1.5; the silicate is sieved through a 300-mesh sieve; the diatomaceous earth is a mixture of diatomaceous earth with a particle size of 5 to 15 μm and diatomaceous earth with a particle size of 20 to 40 μm in a mass ratio of 1:3; silicon carbide, aluminum oxide and ceramic micropowder are all sieved through a 300-mesh sieve; the particle size of kaolinite is 50 to 200 nm; In step (2), the organosilicon resin is one or a mixture of two or more polyalkyl aryl organosilicon resins; sodium fluorosilicate and sodium zirconate are both sieved through a 300-mesh sieve; the diluent is acrylic acid; the stabilizer is calcium stearate; the suspending agent is sodium hydroxymethyl cellulose; the adhesive is polyester phosphate; the rust dissolving agent is hydrofluoric acid; and the preparation method of the acrylic emulsion is: Step (2-1), firstly adding sodium dodecylbenzene sulfonate and nano silicon oxide powder into water, heating to 50° C. and stirring to obtain a mixed suspension; the mass fraction of sodium dodecylbenzene sulfonate in the mixed suspension is 8wt%, the mass fraction of nano silicon oxide powder is 15wt%, and the particle size of the nano silicon oxide powder is 20 to 50nm; Then, butyl acrylate, methacrylic acid, ethylene glycol dimethacrylate, acrylamide and vinyl trimethoxysilane are simultaneously added dropwise to the mixed suspension within 30 minutes and stirred evenly to obtain a pre-emulsion; the mass ratio of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate is 1:0.5:0.08; the amount of acrylamide is 3% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the amount of vinyl trimethoxysilane is 6% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; Step (2-2), firstly adding sodium dodecylbenzene sulfonate into water, heating to 70° C. and stirring to obtain a translucent solution; in the translucent solution, the mass fraction of sodium dodecylbenzene sulfonate is 10wt%; Then, butyl acrylate, methacrylic acid, ethylene glycol dimethacrylate, acrylamide and ammonium persulfate solution are simultaneously added dropwise to the translucent solution and stirred evenly to obtain a seed emulsion; the mass ratio of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate is 1:0.5:0.08; the amount of acrylamide is 3% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the amount of ammonium persulfate solution is 1.0% of the total mass of butyl acrylate, methacrylic acid and ethylene glycol dimethacrylate; the ammonium persulfate solution is an ammonium persulfate aqueous solution with a mass fraction of 10wt%; Step (2-3), raising the temperature of the seed emulsion to 90° C., and simultaneously dropping a 10wt% ammonium persulfate solution and the pre-emulsion prepared in step (2-1) into the seed emulsion and keeping the temperature for 30 minutes, and naturally cooling to room temperature after the reaction is completed, so as to obtain an acrylic emulsion; the amount of the ammonium persulfate solution is 3% of the total mass of the seed emulsion; and the mass ratio of the amount of the pre-emulsion to the seed emulsion is 1:7.